This preview shows page 1. Sign up to view the full content.
Unformatted text preview: k [ sak 1 ( n + )] = namely k 1 = and k 2 = sa n + ( 1 1 ) Taking a Frstorder Taylor expansion about point k , we have f ( k ) = f ( k ) + f ( k )( k k ) where f ( k ) = sa ( k ) 1 ( n + ) and f ( k ) = Consider Frst k = k 1 = 0, then f ( k 1 ) = lim k f ( k ) = lim k [ sak 1 ( n + )] = Next consider k = k 2 > 0, then f ( k 2 ) = 0 and f ( k 2 ) = sa ( k 2 ) 1 ( n + ) = sa sa n + ( 1 1 ) 1 ( n + ) = ( n + ) ( n + ) = ( n + )(1 )...
View Full
Document
 Fall '11
 Dr.Gwartney
 Economics

Click to edit the document details